Mindful marketing and strategic management : paving a sustainable society through past, present, and future perspectives - Jee, Teck Weng; Lau, Evan; Kilgour, Mark (Emerald Publishing Limited, 2025)
Mindfulness has gained significant traction within the business community worldwide. Mindful Marketing and Strategic Management focuses on current advancements in the realm of mindfulness and its application for both effective marketing and strategic management practices. It presents readers with techniques to adopt mindfulness as a major driver for long-term success This edited book includes various strategies for marketers and practitioners to engage customers in a thoughtful and meaningful way. Businesses that use a mindful approach may develop true relationships with their target audience, encourage positive consumer behaviour and loyalty, and have a beneficial social effect through their products or services. The book is a great resource for management and practitioners as it provides practical tools and approaches for incorporating mindfulness into effective strategic management practices, such as leadership and workplace culture, which is vital for organisational success and employee wellbeing. The book provides suggestions on how to incorporate mindfulness into strategic planning, decision-making processes, and team cooperation. By using a mindful approach, practitioners may improve their efficacy, inventiveness, and overall performance, eventually contributing to long-term corporate success.
Includes index.
Keywords: Strategic planning.; Business & Economics -- Strategic Planning.; Business strategy.; elektronické knihy; electronic books